Architecture and sound : an acoustic analysis of megalithic monuments in prehistoric Britain - Watson, Aaron
Prehistoric monuments in Britain are often dominant features in the landscape, and archaeological theory has tended to consider the visual and spatial influences of their architecture upon peoples' movement and perception. The articulation of sound within these structures has not been widely discussed, despite evidence which suggests that many monuments provided settings for gatherings of people. This possibility was explored at two contrasting sites in Scotland, a recumbent stone circle and a passage-grave, revealing that the elemental acoustic properties inherent in each may have literally orchestrated encounters with the stones.